Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1016/j.yhbeh.2006.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Physiological stress levels predict survival probabilities in wild rabbits

Abstract: Among vertebrates, short-term elevations of glucocorticoid hormones (corticosterone or cortisol) facilitate a suite of physiological and behavioral changes aimed at overcoming environmental perturbations or other stressful events. However, chronically elevated glucocorticoids can have deleterious physiological consequences, and it is still unclear as to what constitutes an adaptive physiological response to long-term stress. In this study, we experimentally exposed European wild rabbits Oryctolagus cuniculus t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
130
6
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(143 citation statements)
references
References 31 publications
6
130
6
1
Order By: Relevance
“…Recent studies in wild populations of mammals, birds, and reptiles have reported associations between baseline (18) or chronic (6, 7) GC levels and survival. However, this association is ultimately confounded by differential exposure to stressors among individuals, affecting circulating GC levels, or relates to short-term survival (7). In contrast, our results relate long-term survival and recruitment to the nature of an individual's physiological response to a standardized source of stress.…”
Section: Resultscontrasting
confidence: 63%
“…Recent studies in wild populations of mammals, birds, and reptiles have reported associations between baseline (18) or chronic (6, 7) GC levels and survival. However, this association is ultimately confounded by differential exposure to stressors among individuals, affecting circulating GC levels, or relates to short-term survival (7). In contrast, our results relate long-term survival and recruitment to the nature of an individual's physiological response to a standardized source of stress.…”
Section: Resultscontrasting
confidence: 63%
“…the corticosteronefitness hypothesis [145], through infertility, impaired resistance to disease and inhibition of growth [49,84]. In contrast, other studies suggest that elevated corticosterone promotes adaptive advantages to the individual forming the corticosterone-adaptation hypothesis, [131,146]. Experimental manipulations of corticosterone reveal the complexity of the relationship between corticosterone and fitness.…”
Section: Hormonal Effects On Components Of Fitnessmentioning
confidence: 99%
“…In some years, exogenous corticosterone implants may have a positive effect on total clutch mass and survivorship in females and a negative effect in others [147]. These differences could be explained by a quadratic relationship between corticosterone and fitness [146]. A reduced corticosterone level may indicate acclimatization allowing individuals to maintain good body condition and will not be sufficient to produce a stress-mediated phenotype to cope with a novel environment and consequently suffer lower survival.…”
Section: Hormonal Effects On Components Of Fitnessmentioning
confidence: 99%
“…Cortisol is usually determined in samples of blood (Szeto et al, 2004;de Prada et al, 2007;Cabezas et al, 2007), faeces (Szeto et al, 2004), urine (Walker et al, 2007), milk (Gygax et al, 2006) and saliva (Negrao et al, 2004). Cortisol measurements over a longer period of time, weeks or months, can be taken in hair samples.…”
mentioning
confidence: 99%